HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG DEMAM DENGAN PENANGANAN DEMAM PASCA IMUNISASI TERHADAP ANAK 0-24 BULAN - Bayin Igayanti, Isna; Sylvia Puspita; Haryono, Deddi; Rusdianah, Eva (Jurnal Biogenerasi, 2025)
The aim of this study was to determine the relationship between the mother's level of knowledge about fever and the treatment of post-immunization fever in children aged 0-24 months.This research uses a correlational design with a cross sectional approach. The population in this research was 60 respondents. The sampling technique used was proportional simple random sampling with a sample size of 53 respondents. This study used the spearment rank test to determine the relationship between the mother's level of knowledge about fever and the treatment of fever after immunization in children aged 0-24 months. Research shows that the majority of mothers have a sufficient level of knowledge about fever, with 19 respondents (35.8%). Most of the post-immunization fever handling behavior was in the adequate category, 22 respondents (41.5%). The results of the bivariate analysis show that the mother's level of knowledge about fever and post-immunization fever management is P-value = 0.000 < α = 0.05 with an r value = 0.682, which means that it can be concluded that if the mother's knowledge level about fever is high then the post-immunization fever handling behavior is high. .The results of this research show a relationship between the level of maternal knowledge about fever and the treatment of post-immunization fever in children aged 0-24 months. From this research, it is hoped that mothers will gain more insight into fever knowledge so that mothers' behavior in handling fever after immunization will be good.